2012
DOI: 10.1111/j.1365-263x.2011.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of a ‘bleach‐etch‐seal’ deproteinization technique on MIH affected enamel

Abstract: The findings suggest that there was no significant difference in the tag quality between the conventional technique (Control) and the 'bleach-etch-seal' technique (Treatment 1). There was no benefit in pre-treating with NaOCl alone (without etch) before sealing. This research also showed that there was a high-predicted probability of obtaining 'poor' sealant tags in MIH enamel, regardless of which of the three treatments was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 17 publications
0
29
0
2
Order By: Relevance
“…It is postulated that etching helps to increase access into the enamel to facilitate protein breakdown by NaOCl, putatively allowing better infiltration of the bonding agent and improved bonding to hypomineralised enamel. A recent study on hypomineralised enamel found a high predictability of obtaining ‘poor’ fissure sealant resin sealant tags and no difference in tag quality when 5% NaOCl was added to pre‐etching and sealing . The use of NaOCl post‐etching rather than pre‐etching and the additional use of a bonding agent prior to sealing could possibly have improved tag quality in this study – further research is warranted …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…It is postulated that etching helps to increase access into the enamel to facilitate protein breakdown by NaOCl, putatively allowing better infiltration of the bonding agent and improved bonding to hypomineralised enamel. A recent study on hypomineralised enamel found a high predictability of obtaining ‘poor’ fissure sealant resin sealant tags and no difference in tag quality when 5% NaOCl was added to pre‐etching and sealing . The use of NaOCl post‐etching rather than pre‐etching and the additional use of a bonding agent prior to sealing could possibly have improved tag quality in this study – further research is warranted …”
Section: Discussionmentioning
confidence: 72%
“…A recent study on hypomineralised enamel found a high predictability of obtaining 'poor' fissure sealant resin sealant tags and no difference in tag quality when 5% NaOCl was added to preetching and sealing. 21 The use of NaOCl postetching rather than pre-etching and the additional use of a bonding agent prior to sealing could possibly have improved tag quality in this studyfurther research is warranted. 21,22 In this study, it was found that the greatest bond strengths to hypomineralised enamel occurred when the enamel was pre-treated with NaOCl followed by resin infiltration.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The authors reported a statistically significant difference between group II (restoration without deproteinization) and group III, which suggests that in cavities without removal of all hypomineralized enamel sodium hypochlorite may help in achieving better bond strength although preventing major tissue loss. However, further research is required in order to evaluate the clinical efficacy of this technique because just a few studies on this topic have been conducted …”
Section: Discussionmentioning
confidence: 99%
“…One of them uses artificially demineralized enamel and, therefore, it is not going to be taken into consideration at this point. The first study in 2012 by Gandhi et al investigates the tag formation between the conventional technique of 'etch and seal' and the incorporation of 2.5% NaOCl with or without etching 26 . There was no significant difference between the etch-seal and the bleach-etchseal technique and no benefit from using only NaOCl without etching 26 .…”
Section: A) Etching and Pretreatmentmentioning
confidence: 99%